PENDIDIKAN TRADISIONAL SEBAGAI UPAYA PREVENTIF DALAM PRAKTEK KEKERASAN ANAK - FADHLI, ASHABUL (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2014)
The Constitution of 1945 instructs that education essentially humanize human beings. Briefly, it means that education on one side should be a source of strength against any process of dehumanization without discriminative attitude that often threatens the education and future of children. On the other hand, the source of power that allows humans to develop the whole of nature and its potential as a moral and dignified creature; which in turn became the basis of the formation of a great noble nation.